Associação entre qualidade do sono e polimorfismos dos genes COMT, HTR2A e FKBP5 em pacientes com e sem deformidade dentofacial - Flores, Elvira Katherine Barriga (2020)
INTRODUCTION: Sleep is a fundamental biological function in the consolidation of memory. Sleep disturbances can cause significant changes in the individual's physical, occupational, cognitive and social functioning, in addition to substantially compromising sleep quality. OBJECTIVE: The aim of this study was to associate sleep quality with the polymorphisms of the COMT, HTR2A and FKBP genes in patients with and without dentofacial deformity. MATERIALS AND METHODS: The total sample consisted of 227 individuals divided into a case group and a control group. For the case group, a total of 67 individuals with dentofacial deformity were included, 27 with Facial Profile II and 40 with Facial Profile III. The CONTROL group was composed of 160 patients without dentofacial deformity. The University of Toronto SAQ “Sleep Assesment Questionnaire” questionnaire was applied to record the presence or absence of sleep disorders. In addition, for the genetic evaluation, cells from the oral mucosa were collected through mouthwashes with a 3% glucose solution for two minutes, selecting markers from the COMT genes (rs174675, rs165656); HTR2A (rs4941573, rs6313); and FKBP5 (rs1360780, rs3800373) by means of the PCR technique in real time. The data obtained were cataloged and submitted to statistical analysis with a significance level of 0.05. RESULT: There are several factors that contribute to the alteration or not of sleep. The sleep quality of the subjects in this study was not associated with age. Women have a worse perception of sleep quality in general SAQ and in the domains related to non-restorative sleep, disturbed sleep time, daytime sleepiness and restlessness (p <0.05). There is an association between the quality of sleep and the type of facial profile of the individuals (p <0.05). Facial profile I and II individuals have a worse perception of sleep quality in general and domains related to non-restorative sleep, disturbance of sleep time and restlessness, compared to profile III individuals. In addition, facial profile II individuals had a worse perception of sleep apnea compared to facial profile III (p = 0.034). In the genetic evaluation including all study participants, it was only possible to observe an association between the COMT rs174675 polymorphism and the domain related to restlessness. Homozygous C individuals have a worse perception of sleep quality in this domain compared to heterozygous CT individuals (p = 0.035). In the genetic analysis only of patients with Dentofacial Deformity, there was an association between the rs1360780 polymorphism of the FKBP5 gene and the SAQ domain related to insomnia. That is, individuals who carry the CC genotype have a worse perception in this domain in relation to the CT genotype (p = 0.031). CONCLUSION: Sleep quality is not associated with age, but with the type of facial profile. Women have a worse perception of SAQ. Profile I and II have a worse perception of sleep quality than profile III, while profile II has a worse perception of sleep apnea than profile III. And genetically in the general sample, the COMT marker rs174675 is associated with restlessness (homozygote C has a worse perception than CT heterozygotes). And in the sample case the marker rs1360780 of FKBP5 is associated with insomnia, where the CC genotype has a worse perception of the CT genotype.